What, how, when and who of trial results summaries for trial participants: stakeholder-informed guidance from the RECAP project - Peter Knapp; Katie Gillies; Marion Campbell; Vikki Entwistle; Hanne Bruhn; Rosemary Humphreys; Juliet Tizzard; Sandra Jayacodi (BMJ Open)
Objective To generate stakeholder informed evidence to support recommendations for trialists to implement the dissemination of results summaries to participants.Design A multiphase mixed-methods triangulation design involving Q-methodology, content analysis, focus groups and a coproduction workshop (the REporting Clinical trial results Appropriately to Participants project).Setting Phase III effectiveness trials.Participants A range of participants were included from ongoing and recently completed trials, public contributors, trialists, sponsors, research funders, regulators, ethics committee members.Results Fewer than half of the existing trial result summaries contained information on the clinical implications of the study results, an item deemed to be of high importance to participants in the Q-methodology study. Priority of inclusion of a thank you message varied depending on whether considering results for individuals or populations. The need for personally responsive modes of sharing trial result summaries was highlighted as important. Ideally, participants should be the first to know of the results with regard to the timing of sharing results summaries but given this can be challenging it is therefore important to manage expectations. In addition to patients, it was identified that it is important to engage with a range of stakeholders when developing trial results summaries.Conclusions Results summaries for trial participants should cover four core questions: (1) What question the trial set out to answer?; (2) What did the trial find?; (3) What effect have the trial results had and how will they change National Health Service/treatment?; and (4) How can I find out more? Trial teams should develop appropriately resourced plans and consult patient partners and trial participants on how ‘best’ to share key messages with regard to content, mode, and timing. The study findings provide trial teams with clear guidance on the core considerations of the ‘what, how, when and who’ with regard to sharing results summaries.